2022
DOI: 10.3390/ijerph19127377
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Near-Infrared Technologies to Detect Sentinel Lymph Node in Uterine Cancer: A Prospective Comparative Cohort Study

Abstract: Objectives: Sentinel lymph node biopsy is considered a crucial step in endometrial cancer staging. Cervical injection has become the most favored technique and indocyanine green has been demonstrated to be more accurate than other tracers. Different near-infrared camera systems are currently being used to detect indocyanine green in sentinel lymph nodes and have been compared in different patients. The present study aimed to determine the number and site of sentinel lymph nodes detected in the same patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In a recent meta-analysis by Restaino et al (35), the safety of robotic-assisted surgery was confirmed with a comparable rate of intra-and post-operative complications. In addition, the authors reported similar estimated blood loss quantities between the two groups.…”
Section: Feasibility Of the Robotic-assisted Surgerymentioning
confidence: 87%
See 3 more Smart Citations
“…In a recent meta-analysis by Restaino et al (35), the safety of robotic-assisted surgery was confirmed with a comparable rate of intra-and post-operative complications. In addition, the authors reported similar estimated blood loss quantities between the two groups.…”
Section: Feasibility Of the Robotic-assisted Surgerymentioning
confidence: 87%
“…Nonetheless, very few studies that compared the two minimally invasive approaches in patients with r-ASRM stage III/IV endometriosis are available. To the best of our knowledge, there are only one randomized-controlled trial (RCT) ( 33 ) and two meta-analyses ( 34 , 35 ) in that regard.…”
Section: Feasibility Of the Robotic-assisted Surgerymentioning
confidence: 99%
See 2 more Smart Citations